Effect of combinations of antiviral drugs on herpes simplex encephalitis - Bryan M Gebhardt; Federico Focher; Richard Eberle; et al (Dove Medical Press, 2009)
Bryan M Gebhardt1, Federico Focher2, Richard Eberle3, Andrzej Manikowski4, George E Wright41LSU Eye Center, Department of Ophthalmology, Louisiana State University Health Sciences Center, New Orleans, LA, USA; 2Istituto di Genetica Molecolare, Consiglio Nazionale delle Ricerche, Pavia, Italy; 3Department of Veterinary Pathobiology, Center for Veterinary Health Sciences, Oklahoma State University, Stillwater, OK, USA; 4GLSynthesis Inc., Worcester, MA, USAAbstract: 2-Phenylamino-6-oxo-9-(4-hydroxybutyl)purine (HBPG) is a thymidine kinase inhibitor that prevents encephalitic death in mice caused by herpes simplex virus (HSV) types 1 and 2, although its potency is somewhat less than that of acyclovir (ACV). The present study was undertaken to determine the effect of combinations of HBPG and either ACV, phosphonoformate (PFA), or cidofovir (CDF) against HSV encephalitis. BALB/c mice were given ocular infections with HSV-1 or HSV-2, and treated twice daily intraperitoneally for five days with HBPG, alone or in combination with ACV, PFA, or CDF. Animals were observed daily for up to 30 days, and the day of death of each was recorded. All of the combinations showed additivity, and the combination of HBPG + ACV appeared to be synergistic, ie, protected more mice against HSV-1 encephalitis compared with each drug given alone. Delay of treatment with HBPG for up to two days was still effective in preventing HSV-2 encephalitis. The combination of the thymidine kinase inhibitor HBPG and the antiherpes drug ACV may have synergistic activity against HSV encephalitis. The development of a potent and safe combination therapy for the prevention and/or treatment of HSV infection of the central nervous system can improve the outcome of this infection in humans.Keywords: antivirals, herpetic encephalitis